The evaluation of quality of transformer oil by measuring capacitance - Ahmed, Mukul; Rakib, Md. Enamul Haque (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.